Development, reliability, and validity of the quality of life scale for insomnia: a health-related quality of life instrument for insomnia - Naoko Ayabe; Naoko Ayabe; Isa Okajima; Isa Okajima; Wataru Yamadera; Hisateru Tachimori; Hisateru Tachimori; Hidehisa Yamashita; Naohisa Uchimura; Ken Inada; Yuichi Inoue; Kazuo Mishima; et al. (Frontiers in Psychiatry)
BackgroundInsomnia is a quality of life (QOL) disorder complicated by various mental or physical daytime dysfunctions in addition to nocturnal insomnia symptoms. This study aimed to develop and examine the reliability and validity of a self-administered scale that can sensitively and easily assess QOL disturbances in patients with insomnia.MethodsFrom 122 patients with primary insomnia (mean age 53.8 ± 17.1 years), 11 items correlated with sleep-related clinical indices were extracted and designated the QOL Scale for insomnia (QOL-I). The QOL-I reliability and validity were evaluated.ResultsThe analysis included 93 patients with chronic insomnia (mean age 54.2 ± 16.0 years) and 228 healthy participants (45.0 ± 15.7 years). The QOL-I showed high reliability (Cronbach α=0.92). Factor analysis showed that the QOL-I has a one-factor structure. Correlation analysis between the QOL-I and other variables indicated criterion-related validity (p<0.001).ConclusionThe QOL-I demonstrated good reliability and validity and is expected to be a valuable tool for clinically assessing the QOL of patients with insomnia.